Knowledge based approach for restoration of supply in generation and transmission system - Shen, Wei. (2008)
Bulk power system restoration is a complex, delicate and time-consuming task. This thesis presents the utilization of a knowledge-based system to generate and implement a dynamic restoration plan covering from total blackout up to complete restoration. By reading and comparing the telemetry data, the restoration plan is updated and re-adjusted accordingly.